COMPARATIVE EVALUATION OF EFFECTIVENESS OF CASEIN PHOSPHOPEPTIDE AMORPHOROUS CALCIUM PHOSPHATE AND SODIUM FLOURIDE VARNISH IN DENTINE HYPERSENTIVITY: Dentine Hypersentivity - Abbas, Beenish; Sattar, Madeeha; Abbas, Sana; Rahim, Shoaib; Ishfaque, Qamar; Wajahat, Mehreen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine efficacy of casein phosphopeptide amorphous calcium phosphate and sodium fluoride varnish in managing dentine hypersentivity.Study Design: Quasi-experimental study.Place and Duration of Study: Foundation University College of Dentistry, Islamabad, from Jun to Nov 2020.Methodology: Patients of both gender 20-60 years of age with ASA “American Society of Anesthesiologists physical status classification” status I (completely healthy fit patient) or status II (patient has mild systemic disease) diagnosed with dentine hypersensitivity of incisors, canines, premolars with clinical evidence of erosion, abrasion, gingival recession not requiring restorative treatment were enrolled in the study. At first visit baseline, dentine hypersentivity was recorded by means of tactile and evaporative stimuli, response was quantified using visual analogue scale. Patients were randomly divided in two groups 1-casein phosphopeptide amorphous calcium phosphate, 2-sodium fluoride varnish desensitizing agent was applied conferring to manufacturer instructions. Visual analogue scale readings were assessed at base line and post treatment valueswas recorded at 7th, 15th, 30th day.Results: Total 80 patients enrolled in the study with a mean age of 36.26 ± 8.91 years and age-range of 21-60 years. Visual analogue scale results of group-1 (n=40) were recorded at baseline as 5.9 ± 0 .94, 7th day 1.9 ± 0.92, 15th day 1.4 ± 0 .81 and 30th day 1.0 ± 0.71. In case of group-2 Visual Analogue Score recorded to be 6.2 ± 1.24,3.2 ± 0.81, 3.0 ± 0.52 and 2.7 ± 1.12 at baseline, 7th, 15th, and 30th day respectively.Conclusion: Casein phosphopeptide amorphous..................